2019
DOI: 10.2147/idr.s204880
|View full text |Cite
|
Sign up to set email alerts
|

<p>Community acquired urinary tract infections among adults in Accra, Ghana</p>

Abstract: Background: Urinary tract infection (UTI) is one of the most common bacterial infectious diseases encountered in clinical practice, and accounts for significant morbidity and high medical costs. To reduce its public health burden, there is the need for local research data to address aspects of prevention and management of UTI. The aim of this study was to investigate community-acquired UTI among adults in Accra, Ghana, including the risk factors, etiological agents, and antibiotic resistance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
47
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(60 citation statements)
references
References 41 publications
9
47
3
1
Order By: Relevance
“…The gene bla CTX-M-15 was identified as the determinant of the detected extended spectrum beta-lactamase (ESBL) expression in ESBL positive Enterobacterales [ 23 ]. This is in line with previous reports from both human and livestock-associated ESBL positive Enterobacterales in Ghana [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. In P. aeruginosa and K. pneumoniae , bla SCO-1 , which has initially been described from an Acinetobacter baumannii isolate from Argentina [ 35 ], was observed.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The gene bla CTX-M-15 was identified as the determinant of the detected extended spectrum beta-lactamase (ESBL) expression in ESBL positive Enterobacterales [ 23 ]. This is in line with previous reports from both human and livestock-associated ESBL positive Enterobacterales in Ghana [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. In P. aeruginosa and K. pneumoniae , bla SCO-1 , which has initially been described from an Acinetobacter baumannii isolate from Argentina [ 35 ], was observed.…”
Section: Discussionsupporting
confidence: 92%
“…Thereby, known high-risk clones [ 25 , 26 , 27 ] played only a minor role. Observed resistance patterns and mechanisms were in line with the spectrum expected from previous reports [ 23 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionsupporting
confidence: 90%
“…Assuming minimal Gram-positive etiology in UTIs, this study showed a potential over-diagnosis of UTIs based on clinical assessments, mostly by primary healthcare nurses in CHCs. Such over-misdiagnosis would result in the unnecessary administration of empirical antibiotics, leading to several adverse consequences such as an increase in antibiotic resistance as well as cost to the hospitals and patients [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The loop used transfers an inoculum of 0.002ml. The calibrated loop was used aseptically to transfer specimens on Cystein Lactose Electrolyte Deficient (Rapid Labs) media and incubated aerobically at 37°C for 18-24 hours (Cheesbrough, 2006;Donkor et al, 2019). Following incubation, significant bacterial growth was taken as any count of uniform colonies equal to or in excess of 10 4 CFU per milliliter of urine (Alao and Akintunde, 2012;Emiru et al, 2013;Akter et al, 2014;Mina et al, 2017).…”
Section: Urine Culturementioning
confidence: 99%
“…Some inexpensive screening methods (involving dipstick test and microscopy) are useful in fast detection of people who are at high risk of UTI (Kabugo et al, 2016;Agbagwa and Ifeanacho, 2015). Several research findings at Ghana (Donkor et al, 2019), Cameroun (Charlotte et al, 2019), Iran (Mina et al, 2017), Kenya (Nabbugodi et al, 2015) and Benin (Alfred et al, 2013) have reported on the use of routine macroscopy and microscopy to screen for UTI in pregnancy. It is vital to ensure that pregnant women attain the highest level of health because this goes a long way to determine the outcome of pregnancy (Alfred et al, 2013).…”
Section: Introductionmentioning
confidence: 99%